Respostas
respondido por:
18
a1 + 4r = 18(8)
a1 + 8r = 43(-4)
8a1 + 32r = 144
-4a1 - 32r = -172
4a1 = - 28
a1 = - 7
a1 + 8r = 43(-4)
8a1 + 32r = 144
-4a1 - 32r = -172
4a1 = - 28
a1 = - 7
respondido por:
23
an= a1 + (n-1).r a1+4r= 18
43=18+ (5-1).r a1 + 4. 6,25 = 18
43= 18+4r a1 + 25 =18
43-18=4r a1= 18 - 25
25= 4r a1 = -7
r= 25/4
r= 6,25
43=18+ (5-1).r a1 + 4. 6,25 = 18
43= 18+4r a1 + 25 =18
43-18=4r a1= 18 - 25
25= 4r a1 = -7
r= 25/4
r= 6,25
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás